Kepemimpinan Guru Kristen: Sebuah Tinjauan Etika Kristen - Giofany Junetri; Yesaya Adhi Widjaya (Institut Agama Kristen Negeri Toraja, 2020)
Abstract: The life in contemporary era is full of challenges that have a big impact to almost all aspects in society, including for the growth and development of students in school. Christian teachers should be a role model who keeps on equiping their competencies and grow spiritually in order to be able to lead students. Student in turn is expected to response properly with a true morality when facing all the challenges. Teaches leadership is prominent to be a model for the student to obtain a true morality. This paper will demonstrate the relationship or Christian teacher’s leadership to the growth of student from the ethical perspectives. This paper will examine the essence or nature of Christian teacher, factors affecting, obstacles to Christian teacher leadership, and strategies that can be applied by Christian teacher. The true leadership model is Jesus who provides the meaning and example of leadership with humility within the purpose of God’s Kingdom. By recognizing the true leadership of Jesus Christ, Christian teacher can help students to living out this life through the Christian ethics. This paper will also provide suggestions for further research which will included other aspects in education field. Key Words: Christian teacher, students, leadership, perspective, ethic. Abstrak-Konteks kehidupan zaman ini dipenuhi dengan berbagai tantangan yang memiliki pengaruh yang besar hampir kepada semua aspek kehidupan masyarakat, khususnya bagi pertumbuhan dan perkembangan siswa-siswi di sekolah. Seorang guru Kristen sudah seharusnya menjadi seorang teladan yang secara konsisten menjaga kompetensi dan pertumbuhan spiritual sehingga mampu untuk memimpin siswanya. Siswa diharapkan akan menjadi seorang yang mampu menghadapi realitas hidup ini dengan respon dari moralitas yang benar. Guru adalah teladan pertama yang seharusnya memimpin murid untuk menyadari tentang moralitas yang benar. Makalah ini akan memaparkan kepemimpinan guru Kristen dalam hubungannya dengan pertumbuhan siswa yang ditinjau dari etika Kristen. Makalah ini berisi penjelasan tentang esensi dari natur sebagai seorang guru Kristen, faktor yang mempengaruhi, hambatan atau tantangan menjadi seorang guru Kristen, serta strategi yang bisa di aplikasikan oleh guru Kristen. Model kepemimpinan yang sejati adalah Yesus, yang menyediakan arti dan contoh kepemimpinan dengan kerendahatian dengan kerajaan Allah sebagai tujuannya. Mengakui Yesus sebagai pemimpin yang sejati, seharusnya membuat setiap guru Kriten menyadari untuk kemudian menolong siswanya untuk menghidupi hidup ini berdasarkan etika Kristen. Makalah ini juga menyediakan saran untuk penelitiaan lebih jauh termasuk setiap aspek lingkungan Pendidikan. Kata Kunci: Guru Kristen, peserta didik, kepemimpinan, perspektif, etika